DST ELEMENTS: INFUSION IN THE DEVELOPMENT OF TABLET-BASED TEACHING PRODUCTS (APPS) - Hussain, Hashiroh; Shiratuddin, Norshuhada (Malaysian Journal of Computer Science, 2019)
The usage of instructional media (apps) is poorly delivered due to inappropriate content of the presentation. Recent studies showed that perceptions among students and teachers regarding the use of apps are very low. Thus, Digital Storytelling (DST) concept is infused in developing the apps. Nevertheless, students are unable to comprehend DST clearly. The aim of this study is to identify DST elements for the development tablet based teaching products (apps). Critical analysis and comparative analysis are employed based on eight samples of DST tools to formulate generic DST elements. Eleven DST elements are formed and learning theories are adapted based on correct principles and procedures. The elements should contribute a new pedagogical approach for teachers in developing apps with mobile technology.